O professor coordenador e a percepção que tem da sua função no contexto do programa São Paulo Faz Escola - Martins, Pâmela Carolina do Nascimento (2012)
This study is part of a broader project from the Educational Policy and Management Research Group of PPGE at Universidade Nove de Julho UNINOVE and its main objective is to address the perception that public São Paulo state schools Coordinator Teachers have of their role and attributions in the context of São Paulo Faz Escola Program. Since the Coordinator Teacher has a key role in the implementation of the paulista educational reform of 2007, this study intended to understand how those school agents perceive their routine, along with its challenges, and how policy impact their work. For that matter, we collected data by interviewing eight Coordinator Teachers from five schools and we analyzed it on the grounds of a qualitative research approach. This study brings out the subjective dimension of its subjects who describe their own practice. In order to achieve our objective we sought support in the studies developed by the Advanced Studies in Cognitive and Behavioral Psychology Nucleus (NEAPSI) from the Education School of Universidade Estadual de Campinas (UNICAMP) about Albert Bandura s Social Cognitive Theory and one of its construct, self-efficacy. Thus, we established a connection between the belief of self-efficacy, described by Bandura as a human action mediator, and the Coordinator Teacher s perception of the imposed challenges to his or her position. We also counted on the theoretical support of other authors in the School Management field to enlighten our approach to that management actor. Our research points to the fact that the gaps between the official/prescribed role and the possibilities, urgencies and obstacles of daily practice influence the Coordinator Teachers perception of their role and of how capable they feel to accomplish their tasks.